Transcriptome-Stable Isotope Probing Provides Targeted Functional and Taxonomic Insights Into Microaerobic Pollutant-Degrading Aquifer Microbiota - Bradford, Lauren M.; Vestergaard, Gisle; Táncsics, András; Zhu, Baoli; Schloter, Michael; Lueders, Tillmann (Frontiers in Microbiology, 2018)
While most studies using RNA-stable isotope probing (SIP) to date have focused on ribosomal RNA, the detection of 13C-labelled mRNA has rarely been demonstrated. This approach could alleviate some of the major caveats of current non-target environmental ‘omics. Here, we demonstrate the feasibility of total RNA-SIP in an experiment where hydrocarbon-degrading microbes from a BTEX-contaminated aquifer were studied in microcosms with 13C-labelled toluene under microoxic conditions. From the total sequencing reads (~30 mio. reads per density-resolved RNA fraction), an average of 105 reads per sample were identified as mRNA. Members of the Rhodocyclaceae family (including those related to Quatrionicoccus spp.) were most abundant and enriched in 13C-rRNA, while well-known aerobic degraders such as Pseudomonas spp. remained unlabelled. Transcripts related to cell motility, secondary metabolite formation and xenobiotics degradation were highly labelled with 13C. mRNA of phenol hydroxylase were highly labelled and abundant, while other transcripts of toluene-activation were not detected. Clear labelling of catechol 2,3-dioxygenase transcripts supported previous findings that some of these extradiol dioxygenases were adapted to low oxygen concentrations. We introduce a novel combination of total RNA-SIP and transcript-specific enrichment factors, allowing for a widely applicable and targeted approach to process-relevant gene expression in complex microbiomes.